Scratch como ferramenta em aulas online de cinemática para alunos surdos - Mesquita, Lucas Macedo de (2022)
Given the importance of using visual resources for communication and teaching aimed at the deaf public, and the difficulties encountered when teaching online Physics classes in general, there was a need to use tools to assist in this process. Thus, a project developed in Scratch, initially used in face-to-face classes, was modified and adapted for Remote Teaching, with the objective of helping the teacher during online Physics classes. Therefore, this work has as main objective to qualitatively evaluate the use of Scratch as a tool to assist in the teaching of basic kinematics for deaf students in online Physics classes. This was done through the application of a project produced in Scratch, and the verification of students' opinions regarding the use of this Software through a questionnaire. The methodology of this work is qualitative, as it uses the action research method in which the researcher was directly related to the people and objects of research. With the results achieved, it can be concluded that the program developed in Scratch, in general, had a good performance as a facilitator tool for teaching kinematics for deaf students in the online context. For, it helped the teacher in the transmission of knowledge, helped to generate discussions about the contents during the classes and had a good acceptance by the students.